Changes of esophageal varices in hepatitis C patients after achievement of a sustained viral response by direct‐acting antivirals. Issue 1 (5th July 2021) - Takakusagi, Satoshi; Saito, Naoto; Ueno, Takashi; Hatanaka, Takeshi; Namikawa, Masashi; Tojima, Hiroki; Takizawa, Daichi; Naganuma, Atsushi; Kosone, Takashi; Arai, Hirotaka; Sato, Ken; Kakizaki, Satoru; et al.
Abstract: Objectives: The changes in portal hypertension after achieving a sustained viral response (SVR) by direct‐acting antivirals (DAAs) have not been fully elucidated. Consequently, noninvasive and inexpensive predictors need to be investigated. We therefore explored factors associated with the progression of EVs after the achievement of an SVR with DAAs in patients with chronic hepatitis C. Methods: Eighty‐nine patients, who had achieved an SVR with DAAs and could have their esophagogastroduodenoscopy (EGD) findings compared between before DAAs administration and after achieving an SVR achievement were enrolled in this study. We compared the patients with and without EVs progression. Furthermore, the cumulative progression rates of EVs were also analyzed. Results: The fibrosis‐4 index (FIB‐4) before DAAs administration was the only significant factor for the progression of EVs after an SVR (odds ratios: 1.2, 95% confidence intervals: 1.05–1.38, p = 0.01). In a receiver operating characteristics analysis, the cut‐off of FIB‐4 for the progression of EVs was 8.41 (sensitivity: 0.63, specificity: 0.86, positive predictive value: 0.31, negative predictive value: 0.96), namely EVs of those with more than 8.41 of FIB‐4 progressed and those with less than 8.41 of FIB‐4 did not. Conclusions: As patients with FIB‐4 ≥ 8.41 may have progressions of EVs, periodic surveillance by EGD should be continued in such cases, even after an SVR is achieved.